Bio-child: Human sciences and governing through freedom. (December 2014) - McCallum, David
This article provides an account of the rise of a bio-politics of governing families and children in Australia and its relations with liberal political reason. Drawing on Foucault's lectures on Security, Territory, Population it maps out the ways in which forms of liberal governing seek to define the nature and scope of norms and freedoms in a population through the practices of the human sciences. Bio-politics is shown to introduce new ways of calculating and intervening upon certain parts of the population and to create normalizing tensions with sovereign or judicial forms of governing.